Differences of Fuel and Capacitor Discharge Ignition in Energy Output of Motorcycle - Muhammad Khumaedi; Wahyudi; Muhammad Burhan (HM Publisher, 2020)
The combustion engine is one of the internal combustion engines or often referred to as an internal combustion engine, namely a machine that converts energy thermal energy into mechanical energy. The energy itself can be obtained from the combustion process. One of the simple motorized vehicle transportation tools that are widely used by society today is the motorcycle. The ability of a motorcycle is influenced by several factors, including the quality of the fuel and the ignition system. The use of poor quality fuel can result in a decrease in motorcycle engine performance. Therefore, the selection of the right fuel refers to the compression ratio of each motorcycle. The higher the compression ratio of a motorcycle, the better the quality of fuel it must use.